Teacher research on changing the concept of English language teaching - Ostradický Peter; Kostrub Dušan; Kšiňanová Marína; Hradská Lucia (Journal of Language and Cultural Education)
The presented research conducted at the Faculty of Medicine at Comenius University in Bratislava within the English language course elaborates on the issue of changes in teaching concepts. The research problem was identified based on a specific teaching experience, which indicates that a behavioural approach to teaching and learning is primarily applied in English language classes at the Faculty of Medicine at Comenius University in Bratislava. The concept of constructionist teaching was used, and through qualitative phenomenological research, the student’s perspective on the implemented changes in the teaching process was examined. Focus group tools and phenomenological interviews were used to collect research material. In analysing the research material, the strategy of applying the constant comparison method was utilised. The research sample consisted of 26 students who interpreted their experience with the changed teaching concept, emphasising terms like chaos and fear of the new in their statements. The authors of the study comment on probable causal relationships and point out what is hypothetically possible in the teacher-didactics-learner relationship. Through their research activities, the authors also reflect on currently emphasised intentions, where attention is focused on changes or transformations in teaching strategies, in which the behavioural approach should no longer prevail.